Regional structural change in Argentina (1996–2019): Concepts, measurements and unequal trajectories over the business cycle - Niembro, Andrés Alberto (2024)
Although multiple studies on structural change can be found at the national level, the definition of structural change is far from univocal and its subnational manifestations remain underexplored. This paper empirically examines the patterns of regional structural change in Argentina according to the four main definitions used in the literature (not only productive diversification, predominant in the economic geography field), highlighting the differences that arise when applying these concepts. Based on employment data for 85 labor market areas (LMAs) throughout the 1996-2019 period, we propose different criteria to apply and measure the four definitions and to classify the heterogeneous trajectories of structural change in LMAs, including cluster analysis. As the business cycle is a critical dimension in such an unstable economy, we examine the entire period and compare two sub-periods with very different economic dynamics. The results show that the identification of structural change depends on the concepts and measures used, the unit of analysis (national versus regional) and the type of economic cycle. These findings call for context- and place-based policies.